The acridonecarboxamide GF120918 potently reverses P-glycoprotein-mediated resistance in human sarcoma MES-Dx5 cells - Traunecker, H C L (Nature Publishing Group, 1999)
The doxorubicin-selected, P-glycoprotein (P-gp)-expressing human sarcoma cell line MES-Dx5 showed the following levels of resistance relative to the non-P-gp-expressing parental MES-SA cells in a 72 h exposure to cytotoxic drugs: etoposide twofold, doxorubicin ninefold, vinblastine tenfold, taxotere 19-fold and taxol 94-fold. GF120918 potently reversed resistance completely for all drugs. The EC(50)s of GF120918 to reverse resistance of MES-Dx5 cells were: etoposide 7 ± 2 nM, vinblastine 19 ± 3 nM, doxorubicin 21 ± 6 nM, taxotere 57 ± 14 nM and taxol 91 ± 23 nM. MES-Dx5 cells exhibited an accumulation deficit relative to the parental MES-SA cells of 35% for [(3)H]-vinblastine, 20% for [(3)H]-taxol and [(14)C]-doxorubicin. The EC(50) of GF120918, to reverse the accumulation deficit in MES-Dx5 cells, ranged from 37 to 64 nM for all three radiolabelled cytotoxics. [(3)H]-vinblastine bound saturably to membranes from MES-Dx5 cells with a K(D) of 7.8 ± 1.4 nM and a B(max) of 5.2 ± 1.6 pmol mg(–1) protein. Binding of [(3)H]-vinblastine to P-gp in MES-Dx5 membranes was inhibited by GF120918 (K(i) = 5 ± 1 nM), verapamil (K(i) = 660 ± 350 nM) and doxorubicin (K(i) = 6940 ± 2100 nM). Taxol, an allosteric inhibitor of [(3)H]-vinblastine binding to P-gp, could only displace 40% of [(3)H]-vinblastine (K(i) = 400 ± 140 nM). The novel acridonecarboxamide derivative GF120918 potently overcomes P-gp-mediated multidrug resistance in the human sarcoma cell line MES-Dx5. Detailed analysis revealed that five times higher GF120918 concentrations were needed to reverse drug resistance to taxol in the cytotoxicity assay compared to doxorubicin, vinblastine and etoposide. An explanation for this phenomenon had not been found. © 1999 Cancer Research Campaign